Heterocycle‐linked Phenylbenzyl Amides as Novel TRPV1 Antagonists and Their TRPV1 Binding Modes: Constraint‐Induced Enhancement of In Vitro and In Vivo Activities. Issue 2 (3rd December 2012) - Kim, Nam‐Jung; Li, Fu‐Nan; Lee, Jin Hee; Park, Seul‐gi; Kim, Kyeojin; Lim, Changjin; Han, Young Taek; Yun, Hwayoung; Jung, Jong‐Wha; Park, Hyeung‐geun; Kim, Hee‐Doo; Woo, Byoung Young; et al.
Abstract A series of heterocycle‐linked constrained phenylbenzyl amides were found to be TRPV1 antagonists with promising in vivo profiles. In particular, one of the analogues containing a furan linker exhibited excellent TRPV1 antagonistic activity and in vivo analgesic efficacy. In addition, the binding modes of dibenzyl thiourea, benzylphenethyl amide, and furan‐linked phenylbenzyl amide were examined by using the flexible docking study within the rTRPV1 homology model.